Role of endoplasmic reticulum stress signalling in diabetic endothelial dysfunction and atherosclerosis. (January 2017) - Dong, Yunzhou; Fernandes, Conrad; Liu, Yanjun; Wu, Yong; Wu, Hao; Brophy, Megan L; Deng, Lin; Song, Kai; Wen, Aiyun; Wong, Scott; Yan, Daoguang; Towner, Rheal; et al.
It is well established that diabetes mellitus accelerates atherosclerotic vascular disease. Endothelial injury has been proposed to be the initial event in the pathogenesis of atherosclerosis. Endothelium not only acts as a semi-selective barrier but also serves physiological and metabolic functions. Diabetes or high glucose in circulation triggers a series of intracellular responses and organ damage such as endothelial dysfunction and apoptosis. One such response is high glucose-induced chronic endoplasmic reticulum stress in the endothelium. The unfolded protein response is an acute reaction that enables cells to overcome endoplasmic reticulum stress. However, when chronically persistent, endoplasmic reticulum stress response could ultimately lead to endothelial dysfunction and atherosclerosis. Herein, we discuss the scientific advances in understanding endoplasmic reticulum stress-induced endothelial dysfunction, the pathogenesis of diabetes-accelerated atherosclerosis and endoplasmic reticulum stress as a potential target in therapies for diabetic atherosclerosis.